Buddhist Psychology Intersects with Dance Movement Therapy - Tripura Kashyap; Anubha Doshi; Karishma Arora (Creative Arts in Education and Therapy, 2022)
This article highlights the potential role of the “brahmaviharas,” a Buddhist concept which emphasizes certain spiritual dimensions and have been interlinked with dance movement therapy combined with other expressive arts, in responding effectively to the unpredictable life changes during pandemic situations such as the COVID-19. A multiple therapeutic–expressive–creative movement sequence model and meditation practices were collaboratively developed by movement therapist Tripura Kashyap and expressive arts therapy practitioner Anubha Doshi to address each of the brahmaviharas: loving–kindness (mettā), compassion (karuṇā), sympathetic joy (muditā), and equanimity (upekkhā). This article specifically reveals how the embodiment of concepts from Buddhism through movement can help in concretizing and embedding meditative practices in the mind–body continuum. Finally, the article explores the relevance of practicing the brahmaviharas by utilizing specifically crafted movement rituals, such as body preparatory routines, mindful movement, body scans, embodiment, gratitude rituals, interspersed with visual art and the use of props to focus on enhancing people’s resilience, mental health, and well-being. All these experiences were creatively adapted to the virtual medium during the COVID-19 pandemic period.